Desempenho de motor-gerador de ciclo otto operado com gasolina e biogás proveniente de suinocultura e de uma estação de tratamento de esgotos - Rossetto, Cassiano (2014)
The search for new energy sources that do not pollute the environment as well as the mitigation of environmental impacts caused by population increase, opens a new perspective in the research field of biogas from the wastewater treatment outcome. The process of transformation of energy generated by the combustion of biogas for energy in Otto engines and subsequent transformation into electric energy cycle is easy to perform some adjustments on the motor, this work was being performed only necessary to replace the carburetor by a mixer / air fuel type Venturi. The aim of this study was to evaluate the performance of Otto cycle engine-generator powered with gas from two sources, treatment of human and swine effluent. As witness testing with gasoline were used, simulating different working conditions, with loads of 0; 0.250 kW (10% load); 0.500 kW (20% load); 0.750 kW (30% load); 1 kW (40% load); 1,250 kW (50% load); 1,500 kW (60% load); 1,750 kW (70% load); 2 kW (80% load); 2,250 kW (90% load) and 2,500 kW (100% load). Where emissions of carbon dioxide (CO2), carbon monoxide (CO) and nitrogen oxide (NOx) were evaluated and analyzed the performance of motor-generator that was down around 76% lower when compared with gasoline, and necessary adjustments for better performance.